(untitled) (American Journal of Geospatial Technology, 2024)
The main purpose of this study is to study and evaluate the quality of coal in this region and determine its exploitation potential as an energy source. In this study, bomb calorimeter, dustiness test, and moisture content test experiment were used. So, in this article, the researchers used three articles and four books. Five coal samples were collected from Shurabak region and each of them was analyzed using laboratory analysis methods to determine the quality. The results of the analysis showed that these coals are placed in the category of high quality coals due to their physical and chemical characteristics. The studies show that the region’s coals have a heating value between 4150 and 4545 kcal, an ash percentage of 38 to 44%, a gas percentage of 22 to 28%, and humidity between 0.32 and 0.40%. These values indicate the appropriate quality of coal in the region, which can be used in various industries.Since the brine coal is located in layers of sedimentary rocks including sandstones, conglomerates, argillites, siltstones and carbonate-dolomite, the need for deeper studies to better understand these resources and facilitate their optimal exploitation increases. This research provides a foundation for future studies and practical use of this valuable source of energy.